1983
DOI: 10.1161/01.str.14.4.518
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the measurement of plasma beta-thromboglobulin (beta-TG) in cerebrovascular disease.

Abstract: The plasma concentration of the platelet-specific protein beta-thromboglobulin (beta-TG) was measured in 39 normal subjects and 568 patients of neurological diseases. The beta-TG RIA commercially available KIT was also evaluated. Abnormally high plasma levels of beta-TG were demonstrated in groups of ischemic or obstructive cerebrovascular diseases as compared with that of normal subjects. The highest concentrations were found in 8 patients with Moya-Moya disease, (mean concentration of beta-TG was 204.4 ng/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…31 The high concentrations of vWF:Ag and factor VIII:C and low concentrations of prekallikrein in the NVAF groups are consistent with the findings in previous studies of ischemic cerebrovascular disease. 32^3 The fibrinolytic system seemed to be less involved in this elderly population with stroke than in young patients with stroke or myocardial infarction.…”
Section: Discussionsupporting
confidence: 91%
“…31 The high concentrations of vWF:Ag and factor VIII:C and low concentrations of prekallikrein in the NVAF groups are consistent with the findings in previous studies of ischemic cerebrovascular disease. 32^3 The fibrinolytic system seemed to be less involved in this elderly population with stroke than in young patients with stroke or myocardial infarction.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings in a cohort of men who survived a first MI do not confirm the notion that increased basal platelet reactivity increases the risk of recurrent cardiovascular events. This important negative finding contradicts previous studies which suggested that these inflammatory markers play a role in the development of first and recurrent cardiovascular events [12][13][14][15][16][17]. Regarding the beta-thromboglobulin NAP-2, our findings are in line with the recent study of Berent et al [20], in which no difference in the recurrence of cardiovascular events was found between patients with low and high beta-thromboglobulin levels.…”
supporting
confidence: 55%
“…Regarding the beta-thromboglobulin NAP-2, our findings are in line with the recent study of Berent et al [20], in which no difference in the recurrence of cardiovascular events was found between patients with low and high beta-thromboglobulin levels. A possible explanation for the absence of an association between platelet reactivity markers and recurrent cardiovascular events in our study is that our study population represented a group of stable patients with chronic cardiovascular disease, whereas patients in previous studies were studied in an acute setting [13][14][15][16][17]. However, platelet inflammatory markers might play a more dominant role in the development of cardiovascular events in stable patients with a low prevalence of classic risk factors [12].…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…4 Many studies have shown no significant changes in PF4 or TG with aspirin, [25][26][27] a consistent finding with the present results, but some studies have reported a significant reduction of TG with aspirin. 28,29 A possible explanation for the lack of significant decreases in PF4 and TG by antiplatelet treatment may be that different pathways activate the release of PF4 and TG and the inhibition of one pathway may not be enough to reduce the plasma concentrations of PF4 and TG. 30 In addition to fibrin generation, platelet activation and aggregation have an important role in the process of thrombogenesis.…”
Section: Effects Of Antiplateletsmentioning
confidence: 99%